Albania Country Program Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2021)
This evaluation assesses the development effectiveness of the World Bank Group’s country engagement in Albania over the period Fiscal Years 11-19. The Bank Group made a substantial contribution to many reforms relevant to Albania’s development priorities, including Albania’s EU accession goals. Bank Group support was effective in improving fiscal management and social protection, strengthening the financial sector, and expanding waste management and irrigation. The program was responsive to opportunities, but it could have been more selective in its engagements. Findings suggested that analytical work should be used more extensively to build consensus and capacity for reforms and new lending should be more selective. Albania had transitioned to a market-oriented middle-income economy by year 2008. However, the economic slowdown in the wake of the global crisis led to a reversal in poverty reduction. The crisis led to several key economic reforms, not all of which have been sustained after the recovery.